Study of exponential stability of coupled wave systems via distributed stabilizer - Mahmoud Najafi (International Journal of Mathematics and Mathematical Sciences)
Stabilization of the system of wave equations coupled in parallel with coupling distributed springs and viscous dampers are under investigation due to different boundary conditions and wave propagation speeds. Numerical computations are attempted to confirm the theoretical results.